2018
DOI: 10.1159/000489807
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index (SII) is Useful to Predict Survival Outcomes in Patients After Liver Transplantation for Hepatocellular Carcinoma within Hangzhou Criteria

Abstract: Background: There is growing evidence that the systemic immune-inflammation index (SII), a novel prognostic biomarker based on peripheral lymphocyte, neutrophil, and platelet counts, is associated with poor prognosis for several tumors. However, the prognostic value of SII in patients with hepatocellular carcinoma (HCC) who undergo liver transplantation (LT) remains unclear. The aim of this study was to determine the correlation between SII and prognosis in these patients. Methods: This retrospective study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 26 publications
2
70
1
1
Order By: Relevance
“…This result is contrary to previous studies focusing on other types of malignancies, while a number of studies found a positive result for NLR, PLR, LMR or SII in the role of predicting the survival for cancer patients. 5,[10][11][12][13][16][17][18][19][20][21][22] In fact, these markers also have their theoretical foundations for predicting the survival of cancer patients. For example, neutrophils could produce various factors that could promote tumor cell proliferation and invasion; lymphocytes could mediate cytotoxic cell death and inhibiting tumor cell proliferation and metastasis; monocytes in the peripheral blood reflect the status of TAM in patients, while TAM derived from monocytes inhibit immune response and promote tumor growth; elevated platelet counts could stimulate tumor angiogenesis and promote tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This result is contrary to previous studies focusing on other types of malignancies, while a number of studies found a positive result for NLR, PLR, LMR or SII in the role of predicting the survival for cancer patients. 5,[10][11][12][13][16][17][18][19][20][21][22] In fact, these markers also have their theoretical foundations for predicting the survival of cancer patients. For example, neutrophils could produce various factors that could promote tumor cell proliferation and invasion; lymphocytes could mediate cytotoxic cell death and inhibiting tumor cell proliferation and metastasis; monocytes in the peripheral blood reflect the status of TAM in patients, while TAM derived from monocytes inhibit immune response and promote tumor growth; elevated platelet counts could stimulate tumor angiogenesis and promote tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory indicators are expressed by inflammatory scores, such as neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR), and have been reported to be associated with the prognosis of patients with malignant tumors [8,10,11]. Recently, a new inflammatory index, the systemic immune-inflammation index (SII), defined as neutrophil × platelet/lymphocyte, integrates three inflammatory cells and has been shown to be promising [12]. The prognostic value of SII has been confirmed in various cancers, including NSCLC [13], small cell lung cancer [14], esophageal squamous cell carcinoma (SqCC) [15], breast cancer [16] and hepatocellular cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies had shown that NLR, AFP and brinogen were related to liver cancer patients OS 20,21 . In our study, we used the median of NLR and PLR as their cutoff values,the values were similar to that previously reported 22,23 . To our surprise, hematological indicators such as NLR, PLR and AFP were not prognosis factors of patients DFS.…”
Section: Discussionmentioning
confidence: 84%